Gaya Kepemimpinan Demokratis Kepala Sekolah dalam Mengembangkan Profesionalisme Guru Pendidikan Agama Islam - Muman, Dede; Hanafiah, Nanang; Setiawan, Marwan (An-nida: Jurnal Pendidikan Islam, 2022)
This research departs from an idea about the principal's democratic leadership style that can develop the professionalism of PAI teachers at SMAN 30 Garut. However, even though the principal in his leadership applies a democratic leadership style, there are still PAI teachers who are not yet professional in carrying out their duties as learners. This shows that there is a problem in it. The purpose of the study was to find out about the planning, implementation of the concept and assessment policies and the steps taken by the principal, the inhibiting and supporting factors as well as the solutions and follow-up of the principal in implementing a democratic leadership style to develop PAI teachers. The theological foundations are the Al-Quran and Al-Hadith, the philosophical foundations that form the basis of leadership in accordance with theory. The research method used is a qualitative research method. The data collection techniques were carried out by means of interviews, observations, documentation studies and literature studies. Analysis of the data used in this study using inductive data analysis. From the research, it was concluded that the democratic leadership of the head of SMAN 30 Garut showed a democratic leadership style, (1) Planning by implementing high school curriculum by adopting some of the MA curriculum and creating a school that was in accordance with the declared Vision, Mission and Goals; (2) The implementation is carried out by the principal's efforts to involve and involve all school members (Teachers, Employees and School Committees) to take part in the implementation of school programs in accordance with their respective main tasks and functions; (3) The assessment is carried out by the principal, namely providing control over teacher activities, supervision, seeing teacher preparation and readiness before carrying out the learning process, praise and criticism; (4) Inhibiting factors (teachers, environment, costs, students, learning resources and government policies that do not favor Islamic religious education) and supporting factors (welfare, allowances, certification and rewards); (5) The solution and follow-up are to socialize the rules of the game that apply in schools, control, involve teachers in various scientific activities, seminars and workshops, PAI extracurricular programs, provide welfare, reward and punishment, provide motivation, guidance and direction to students. teachers to achieve maximum educational goals. The researcher conveys a suggestion that the principal should always be dissatisfied with the success that has been achieved, in order to always make innovations and new breakthroughs in developing the professionalism of PAI teachers.